2009
DOI: 10.1111/j.1365-4632.2009.03946.x
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid induces apoptosis by regulating the expression of Bax and Bcl‐2 and enhancing caspase‐3 activity in human malignant melanoma A375 cells

Abstract: GA can inhibit the proliferation of A375 cells and induce their apoptosis, which may be related to the up-regulation of the Bax/Bcl-2 ratio and caspase-3 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…this result is consistent with previous findings that GA induces apoptosis in some other tumor cells by up-regulating the Bax/Bcl-2 ratio (9,10,26,27).…”
Section: Discussionsupporting
confidence: 83%
“…this result is consistent with previous findings that GA induces apoptosis in some other tumor cells by up-regulating the Bax/Bcl-2 ratio (9,10,26,27).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have shown that GA can induce apoptosis in some tumor cells 13,33,34) . Our results suggested that the antiproliferative effect of GA was not due to apoptosis or necrosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1) is the main active ingredient of gamboges secreted from the Garcinia hanburryi tree, which mainly grows in Southeast Asia. GA is known to have extensive antitumor activities in certain solid tumors (3,4). Over the last decade, our group has confirmed that GA exhibits cytotoxicity in various types of hematological malignancy (5,6).…”
Section: Introductionmentioning
confidence: 59%
“…The effect of GA on the proliferation of RPMI-8226 cells was analyzed using the MTT assay. Briefly, cells (2x10 4 ) were seeded in a 96-well plate and treated with 0.5, 1.0, 1.5, 2.0 or 2.5 µM GA for 12 h. Following incubation, 20 µl MTT (5 mg/ml) was added to each well and the cells were incubated for a further 3 h at 37˚C. The supernatant was discarded, 150 µl DMSO was added and the plate was gently agitated until the blue crystals were dissolved.…”
Section: Introductionmentioning
confidence: 99%